62 Effects of forage allowance and supplementation on performance of steers grazing wheat pasture. (28th November 2020) - McNeill, Kynzie; Reuter, Ryan R; Beck, Paul A
Abstract: A 72-d trial was conducted to estimate the combined effect of forage allowance and a fiber-based energy supplement in stocker cattle grazing wheat. Eight pastures (2.7 to 5.1 ha) each contained seven test steers (initial BW = 210 ± 36 kg). Weekly, additional steers were stocked in each pasture in a put and take method to achieve forage allowance of either 2.5 or 5.5 kg forage DM / kg steer BW (4 pastures each). Two pastures in each forage allowance were fed daily with a supplement containing 50% wheat midds and 50% soybean hulls at the rate of 1.5 kg per steer. Forage mass was measured twice weekly using a calibrated rising plate meter. Cattle were weighed weekly on calibrated scales. Data were analyzed using linear regression with pasture as the experimental unit. Mean ADG was 1.36 kg/d. One pasture in the high forage allowance, non-supplemented treatment was removed because we were unable to maintain the designed forage allowance. The interaction of forage allowance and supplement was not significant (P = 0.37) for ADG, and supplementation did not affect ADG (P = 0.20), however increased forage allowance tended to improve ADG (P = 0.06, 0.21 kg ADG per kg forage allowance). To further investigate forage DMI, a 14-d trial began on day 36. Three of the seven test steers in each pasture were randomly chosen and administered 7 ± 0.1 g of TiO2 daily at 0700 as an external marker to estimate fecal output. Forage DMI (at an assumed 72% DM digestibility) averaged 2.1% of midpoint BW, below our expectation. Additional forage allowance tended to improve estimated forage DMI (P= 0.06), but supplement had minimal effect (P = 0.30).